Robotics and Artificial Intelligence in Today's Agriculture - Surekha, Muli Naga; Vasuki, V. (European Journal of Applied Sciences, 2024)
The increasing population poses an ever-increasing demand for food production amidst major constraints like decreasing agricultural labour, increased growth rate of industrialization, urbanization, reduced land and water availability for agriculture, and drudgery in farm works. With rapid development of technology in the field of robotics and AI, has created new horizons for its application in agriculture and allied sectors. These latest technologies help farmers in facing the challenges in food production to ensure food security, environmental sustainability and labour efficiency in the age-old industry. In this review article, a comprehensive view of the current state and future trends of robotics and AI in various agricultural domains, like crop monitoring, weed control, harvesting, sorting and transportation are discussed.